ANALISIS PELAYANAN PUBLIK TERHADAP TINGKAT KEPUASAN MASYARAKAT DI DESA LAGADING KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Fatmawati; Sellang, Kamaruddin; Adnan, Andi Astina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the Public Service Analysis of the Level of Community Satisfaction in Lagading Village, Pitu Riase District, Sidenreng Rappang Regency. The population in this study was 47 people who received services in November and December in Lagading Village, Pitu Riase District, Sidenreng Rappang Regency. The sampling technique uses a saturated sample where the entire population is sampled. This type of research is quantitative descriptive. The data collection techniques used in this research were observation, literature study and questionnaires. The data analysis technique used is validity and reliability testing, using the IBM SPSS statistics 26.0 application. The results of this research showed that the Public Service Analysis from the results of the questionnaire obtained a recapitulation of public service variables of 61% in the